Determinación de la seroprevalencia de brucelosis bovina y de loa factores asociados en el cantón El Pangui provincia de Zamora Chinchipe. - Cruz Castillo, José Manuel (2022)
Bovine brucellosis is an infectious disease caused by Brucella abortus, Gram negative coccoid that mainly affects cattle and se- condarily other animal species (in decreasing order of suscepti- bility can be extended to: sheep, goats, horses, and canines) and humans.The present investigation had in order to determine the seroprevalence and associated factors of bovine brucellosis in the canton of Pangui province of Zamora Chinchipe; 166 samples were processed according to the protocols of the Agency for the Regulation and Control of Fito and Zoosanitary (AGROCALIDAD), for which the serological techniques Rose Bengal and competition ELISA. On the other hand, during the sampling information was obtained information regarding the following variables: origin, race, age, age group, which possible associated factors were considered. 5.42 % of animals were positive in the rose bengal test, however no sample was confirmed by ELISA, so the analysis could not be carried out to establish factors associates. Key words: bovine brucellosis, abortion, zoonosis, immunodiagnosis